Risk factors of infection in neuroendovascular procedure - Shoichiro Ishihara; Hideaki Ishihara (Indian Journal of Neurosurgery)
Background With the advent of neuroendovascular procedures, there has been a revolution in the management of neurovascular diseases. One of the major advantages for this minimally invasive procedure is low rate of infections, as compared to craniotomy for treatment of the diseases. However, the risk of infection in these procedures has not been reported widely in the literature. We studied the risk of infection in neuroendovascular procedures in our experience.